DISCUSSION ON MARINE CAPTURE FISHERIES SURVEY IN VIETNAM - Ha, Vu Viet (Vietnam Journal of Marine Science and Technology, 2018)
In fish stock assessment, two approaches have been used to collect data: Fisheries independent survey and fisheries survey. Fisheries independent survey provides scientific information on species composition, catch rate, density, distribution, standing stock biomass and biological information of certain species while fisheries survey supplies primary data for a wide variety of statistical analysis of fisheries performance. In Vietnam, fisheries survey was first developed by project “Assessment of the Living Marine Resources in Vietnam” with the support of DANIA since 1998 as the pilot study in 11 coastal provinces with the purpose of establishing the fisheries statistical system in Vietnam. After the pilot stage, it has been extended to all of 28 coastal provinces and worked effectively since 2000. In 2006, when the project ended, the fisheries statistical system collapsed due to no finance support to continue. Since July 2014, the fisheries data collection network has been recovered with the collaboration of Directorate of Fisheries, Research Institute for Marine Fisheries and Provincial Departments of Capture Fisheries and Marine Resources Protection. The survey design was the logbook base with applying the sampling in space and in time method. This is an overview of the capture fisheries survey in Vietnam with its limitations and challenges.